Transforming Majelis Taklim into a Hub for Productive and Sustainable Community Development - Evanita, Susi; Syofyan, Rita; Syukur, Yarmis; Fahmi, Zul (LP2M IAIN Palopo, 2025)
The Majelis Taklim, as a non-formal Islamic educational institution, plays a strategic role in enhancing the socio-spiritual and economic capacities of communities. However, its activities often remain confined to religious rituals with limited empowerment outcomes. This community engagement initiative aimed to transform Majelis Taklim Nurul Islam in Air Tawar Barat, Padang City, into a productive and sustainable community through entrepreneurship training, managerial capacity building, digital marketing literacy, and the establishment of a sharia cooperative. Using a participatory and needs-based approach, the program involved lecturers, students, and community members collaboratively. The outcomes revealed significant improvements in entrepreneurial motivation, digital skills, and business organization. The creation of Koperasi Syariah Kacio Mitra Islami symbolized institutionalized community empowerment. This initiative demonstrates the transformative potential of Majelis Taklim as a catalyst for women’s empowerment and sustainable economic development aligned with the Sustainable Development Goals (SDGs) 1, 5, 8, and 9.